Self-Schema, Attachment Style, and Treatment Outcome of Patients in an Opiate Maintenance Treatment Unit - Hovelius, Emelie; Lindén, Ellen; Bengtsson, Hans; Håkansson, Anders (Frontiers in Psychology, 2021)
The aim of this study was to explore self-schemas and attachment style among patients in a methadone or buprenorphine maintenance treatment program of opiate dependence, in relation to treatment outcome (relapse in substance use). The study included 84 patients (21 women and 63 men) in a psychiatric clinic in Malmö, Sweden, providing maintenance treatment of opiate dependence. Three self-report instruments were employed, Young Schema Questionnaire Short version (YSQ-S) and Young Parenting Inventory (YPI) for studying self-schemas and Experiences in Close Relationships–Relationship Structures questionnaire (ECR-RS) for studying attachment style. Demographical data and relapse in substance abuse were registered. The study demonstrated, unsurprisingly, that an insecure attachment style was more common in the group of patients compared to available general population reference data. Significant correlations were found between attachment style and core beliefs about the self (self-schemas). Memories of parenting experiences from childhood (YPI) showed correlations with ongoing self-schemas (YSQ-S). Treatment outcome, defined as relapses in substance abuse, was associated to a minor degree with self-schemas but showed no correlation with attachment style. Patients who did not work or study had more maladaptive self-schemas and insecure attachment style, and a higher incidence of relapse in abuse than patients who were working or studying.